2020
DOI: 10.1002/anie.202010995
|View full text |Cite
|
Sign up to set email alerts
|

A New Mechanically‐Interlocked [Pd2L4] Cage Motif by Dimerization of two Peptide‐based Lemniscates

Abstract: Most metallo-supramolecular assemblies of low nuclearity adopt simple topologies, with bridging ligands spanning neighboring metal centers in a direct fashion. Here we contribute a new structural motif to the family of host compounds with low metal count (two) that consists of a pair of doubly-interlocked, Figure-eight-shaped subunits, also termed "lemniscates". Each metal is chelated by two chiral bidentate ligands, composed of a peptidic macrocycle that resembles a natural product with two pyridyl-terminated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 104 publications
0
23
0
2
Order By: Relevance
“… 60 Recently, we contributed a [Pd 2 L 4 ] host with a new mechanically-interlocked motif, consisting of a pair of doubly-interlocked, figure-eight-shaped lemniscates. 30 Even higher complexity was reported by Lützen and co-workers, with a rotaxane-like cage-in-ring structural motif, where a BODIPY-based bis-pyridine ligand ( 1 ) self-assembles with Pd II cations to form a compound of [Pd 6 1 12 ] stoichiometry ( Fig. 3a ).…”
Section: Increasing Structural Complexitymentioning
confidence: 82%
See 1 more Smart Citation
“… 60 Recently, we contributed a [Pd 2 L 4 ] host with a new mechanically-interlocked motif, consisting of a pair of doubly-interlocked, figure-eight-shaped lemniscates. 30 Even higher complexity was reported by Lützen and co-workers, with a rotaxane-like cage-in-ring structural motif, where a BODIPY-based bis-pyridine ligand ( 1 ) self-assembles with Pd II cations to form a compound of [Pd 6 1 12 ] stoichiometry ( Fig. 3a ).…”
Section: Increasing Structural Complexitymentioning
confidence: 82%
“… 29 Organic bridges are multitopic ligands with two or more donors of same or differing chemical structure and a backbone that determines size and shape of the assembly and can carry extra functional or solubilizing groups. While the individual donor groups can be mono- or multidentate, ligands are usually designed not to chelate the same metal so they serve as bridges between different metal nodes (a recent notable exception is a cavity formed by a pair of mechanically entangled “figure-eight”-shaped Pd II -chelate complexes 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…Examples of the use of the IM‐MS technique have been reported for supramolecular coordination complexes (SCCs) supported by N‐, O‐ donor, Werner‐type ligands, and include topological characterization studies [7] and the identification of geometric isomers [8] . Furthermore, recent studies showed that IM‐MS could be used to visualize the expansion and contraction of chiral palladium cages upon addition of different guests [7l,m] …”
Section: Methodsmentioning
confidence: 99%
“…Note that the synthetic parameters for this analysis do not include those related to the reactions that prepare the starting materials. For example, some procedures for the formation of CCs involve anion exchange reactions of metal salts before adding the ligand [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. This process is excluded from the meta-analysis to compare only the quantitative comparison of the reaction time and temperature, "immediate" and "overnight" were interpreted as 1 min and 12 h, respectively.…”
Section: Comparison Between Ccs and Mocs In The Reaction Time Against...mentioning
confidence: 99%